A Shadow-Rate Term Structure Model for the Euro Area - Wolfgang Lemke; Andreea Vladu (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We model the dynamics of the euro area yield curve using a shadow-rate term structure model (SRTSM), with particular attention to the period since late 2011 when interest rates have been at the lowest level since the inception of EMU. The shadow rate is driven by latent factors with linear Gaussian dynamics, while the actual short rate is the maximum between the shadow rate and a lower bound (estimated at 10 bps) so that interest rates will never fall below that level. The estimated SRTSM performs attractively with respect to cross-sectional fit and forecast performance. The model implies that since mid-2012 the median horizon when future one-month rates would return to 50 bps has been ranging between about 25 and 40 months. Deriving such lift-off timing instead from the simple metric of the forward curve crossing 50 bps would underestimate the SRTSM-implied median timing by between 5 to 15 months. As a novelty in the literature, we analyze the effect of a downward shift in the lower bound on the yield curve: for short maturities, rates decrease one-to-one with a drop in the lower bound, while the effect diminishes for longer maturities. The shift-down in the euro area yield curve between April and June 2014 appears to partially reflect such a drop in the (perceived) lower bound.
Keywords: G12; C32; E43; 330